Evaluation of cytotoxicity and migratory effect of aqueous extract of Baeckea frutescens Lin. on keratinocytes / Ihsan Safwan Kamarazaman ... [et al.] - Kamarazaman, Ihsan Safwan; Nik Hasan, Mohd Kamal; Adnan, Nur Nazihah; Khotib, Siti Sarah; Maniam, Sandra; Halim, Hasseri (Faculty of Applied Sciences, 2024)
Wounds, especially chronic wounds, have become a global problem affecting the quality of life, economic welfare, and productivity. Like fibroblast and endothelial cell migration, Keratinocyte migration has been associated with the wound-healing properties of certain compounds, fractions, or plant extracts. This study aimed to investigate the cytotoxicity and migration effect of the aqueous extract of Baeckea frutescens (BFAE) on immortalized human keratinocytes (HaCaT). Cytotoxicity was assessed using the MTT tetrazolium reduction assay, and the viability of HaCaT treated with 7.81–1000 μg/ml BFAE was determined. The migratory effect of BFAE at concentrations of 0, 1, 5, and 10 μg/ml was determined by scratching assay, and the comparison of migration rate between 0 and 12 hours was evaluated. The results indicate that BFAE is not cytotoxic when treated at concentrations of 200 μg/ml and below, when it has a cell viability greater than 80 %, compared to the untreated cells. BFAE also showed a migratory effect on HaCaT when it increased the migration of HaCaT by 1.3-fold when treated with 1 and 5 μg/ml BFAE, respectively. These results demonstrate the wound-healing properties of BFAE, which may be a very good candidate for a plant-derived wound-healing product.